Relativistic gravimetry - С.А. Матвієнко (Геофизический журнал, 2022)
Work on the creation of a device that will be able to measure the parameters of the Earth’s gravitational field in space was started at the State Design Office «Yuzhnoye» in 2001 as part of the formation of a scientific research program on the «Sich-1M» spacecraft. But since there were no devices in the world to directly measure the parameters of the Earth’s gravitational field in space, the idea arose to use the relativistic «red shift» effect to solve this problem. The possibility of practical implementation of this idea arose in 2008—2010 during the implementation of the STCU project No. 3856 «Measurement of the parameters of the Earth’s gravitational field using navigation satellite systems». Within the framework of this project, for the first time, a differential radiophysical gravimeter was created and tested, in which the radiation of navigation satellites was used as a source of highly stable radiation. Radiophysical method for measuring the parameters of the Earth’s gravitational field based on the results of dissertation research, 4 patents for an invention of Ukraine, 2 copyright certificates were obtained, and 16 articles were published in scientific journals. In 2012, the fundamental patent No. 98358 «Method for measuring geodetic parameters and a device for its implementation» was obtained, which was recognized in 2014 as the best patent of Ukraine in the absolute nomination in the competition «Best Patent of Ukraine». This patent formed the basis for the creation of the «Gravika» — navigation control and correction station. This work has been continued at JSC «RPC «KURS» since 2015. Since 2015, JSC «RPC «KURS» has been the head organization in the NSAU for the creation of a coordinate-clock and navigation support network for Ukraine. In 2016, it was created, certified and put into operation control and correction station (CCS) «Gravika», which can simultaneously operate both as a navigational base station and as a gravimeter, that is, to solve a complete geodetic problem. The principle of operation of the gravimeter is based on the relativistic effect of «red shift». One of the main technical and economic problems is the need to use a highly stable hydrogen frequency standard as part of the Gravika control and correction station, the cost of which is at least USD 80,000 (code «Geomonitoring») in order to develop a concept for creating, on the basis of the existing network of coordinate-clock and navigation support in Ukraine, a complex a clear geophysical monitoring system using the Gravika control and correction station and a satellite system for relaying signals of a highly stable TWSTFT frequency standard. Such a solution will make it possible to abandon the use of a frequency standard at each station and thereby reduce the cost of the CCS and the system as a whole. In addition, the work of the CCS «Gravika» showed the possibility of predicting seismic activity within a radius of 500 km from the station. A three-axis version of the gravimeter was also implemented, which allows you to simultaneously measure the absolute, relative values of the gravitational acceleration and the angle of inclination of the gravitational acceleration vector. Such functionality makes the radiophysical gravimeter indispensable when used on mobile vehicles, including space vehicles.